Practical research : planning and design - Leedy, Paul D.; Ormrod, Jeanne Ellis (Pearson, 2016)
A broad-spectrum, cross-disciplinary book suitable for a wide variety of courses in basic research methodology. The eleventh edition features new strategies in research methodologies, updated discussions of technology-based strategies, and the clarification and restructuring of all material.